On vampire squid and pie in the sky - Reflections on greed, altruism, global capitalism, Muslim and other ethics - Mark Woodward (International Journal of Interreligious and Intercultural Studies, 2021)
This article points to some of the ethical short-comings of global capitalism in historical and contemporary contexts. Comparison of late eighteenth/early nineteenth century capitalist enterprises including the British and Dutch East India Companies and contemporary investment banking houses including Goldman Sachs indicates that ethical problems inherent in global capitalism have not changed significantly over the centuries. The analysis presented here builds on explicit critiques of capitalism by the eighteenth-century economist Adam Smith and contemporary critiques by linguist and social critic Noam Chomsky and implicit ones Reggae star Jimmy Cliff. Islamic finance is often described as an alternative to capitalisms that avoid greed based ethnical problems. This is not necessarily the case if Islamic finance is merely fiqh compliant. The fact that Goldman Sachs and other Western banks have entered the Islamic finance business buttresses this position. The economic ethics of the eleventh/twelfth century Muslim theologian and philosopher Hamid al-Ghazali and the contempory Muslim legal scholar Khaled Abou el Fadl offer possible correctives. If, however, Evolutionary biologist Lynn Margulis is correct and greed is a basic component of human nature, the full realization of any ethical economics is unlikely.